Biphasic regulation of the transcription factor ABORTED MICROSPORES (AMS) is essential for tapetum and pollen development in Arabidopsis - Ferguson, Alison; Pearce, Simon; Band, Leah R.; Yang, Caiyun; Ferjentsikova, Ivana; King, John; Yuan, Zheng; Zhang, Dabing; Wilson, Zoe A. (Wiley, 2016)
Viable pollen is essential for plant reproduction and crop yield. Its production requires coordinated expression at specific stages during anther development, involving early meiosis-associated events and late pollen wall formation. The ABORTED MICROSPORE (AMS) transcription factor is a master regulator of sporopollenin biosynthesis, secretion and pollen wall formation in Arabidopsis. Here we show it has complex regulation and additional essential roles earlier in pollen formation. • An inducible-AMS reporter was created for functional rescue, protein expression pattern analysis and to distinguish between direct and indirect targets. Mathematical modelling was used to create regulatory networks based on wildtype RNA and protein expression. • Dual activity of AMS was defined by biphasic protein expression in anther tapetal cells, with an initial peak around pollen meiosis and then later during pollen wall development. Direct AMS-regulated targets exhibit temporal regulation, indicating additional factors are associated with their regulation. • We demonstrate that AMS biphasic expression is essential for pollen development and defines distinct functional activities during early and late pollen development. Mathematical modelling suggests AMS may competitively form a protein complex with other tapetum-expressed transcription factors, and that biphasic regulation is due to repression of upstream regulators and promotion of AMS protein degradation.